2016
DOI: 10.1177/0883073816681257
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship of Exposure to Anesthesia on Outcomes in Children With Isolated Oral Clefts

Abstract: This study evaluated the relationship between exposure to anesthesia and previously identified differences in cognitive functioning, growth, and volumetric brain measures among a sample of children, adolescents, and young adults with isolated oral clefts (iCL/P). Data from a cross-sectional study was combined with a retrospective chart review. Data was obtained for 87 participants with iCL/P (55% male), ranging from 7.5 to 27 years old (mean = 15.78 [SD = 4.58]). Measures of interest included cognitive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
(67 reference statements)
1
22
0
1
Order By: Relevance
“… 19 This directly addresses patients with CLP because most of them undergo cheiloplasty and/or PP between 6 and 12 months after birth in an effort to optimize feeding and speech outcomes. 20 Conrad et al 21 found that recurrent exposure to anesthesia can result in impaired cognitive growth and frontal lobe development. Additionally, they observed that pediatric patients with an isolated cleft lip who underwent several procedures were more likely to present with decreased verbal intelligence quotient (IQ).…”
Section: Discussionmentioning
confidence: 99%
“… 19 This directly addresses patients with CLP because most of them undergo cheiloplasty and/or PP between 6 and 12 months after birth in an effort to optimize feeding and speech outcomes. 20 Conrad et al 21 found that recurrent exposure to anesthesia can result in impaired cognitive growth and frontal lobe development. Additionally, they observed that pediatric patients with an isolated cleft lip who underwent several procedures were more likely to present with decreased verbal intelligence quotient (IQ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have used a variety of specific assessment tools, or parts hereof, to evaluate different criteria within development, cognition, intelligence, academic achievement, and neuropsychological diagnosis. Comparatively, few studies have assessed outcomes such as neuroimaging, 18,35,48,49,56,63 mortality, or serum-biomarkers. 18,19,22,38,39,42,44,48 Previously, it has been questioned which criteria are suitable outcome measures in studies on long-term neurocognitive Table 3 Risk of bias evaluation; A-I represents rating categories according to Newcastla-Ottawa Scale for assessing quality of non-randomised studies.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, few studies have assessed outcomes such as neuroimaging, 18,35,48,49,56,63 mortality, or serum-biomarkers. 18,19,22,38,39,42,44,48 Previously, it has been questioned which criteria are suitable outcome measures in studies on long-term neurocognitive Table 3 Risk of bias evaluation; A-I represents rating categories according to Newcastla-Ottawa Scale for assessing quality of non-randomised studies. A, Representativeness of the exposed cohort; B, Selection of the non-exposed cohort; C, Ascertainment of exposure; D, Outcome of interest was not present at start of study; E, Comparability of cohorts -major factor controlled for; F, Comparability of cohorts -any additional factor controlled for; G, Assessment of outcome; H, Follow-up long enough for outcome to occur?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected children are required to take time off school to undergo surgery to repair the cleft (a study in the United States showed that roughly 24% of surgeries to repair CL and 37% of surgeries to repair CP are secondary surgeries, and roughly 70% of those occur during school ages 44 ), and to attend follow-up health assessments, which could affect their learning. There is some observational evidence that repeated surgery (and therefore repeated exposure to general anaesthesia) is associated with lower IQ in children born with a cleft 21,45 .…”
Section: Comparison To Previous Evidencementioning
confidence: 99%